A Microfluidic Ion Sensor Array. Issue 6 (22nd January 2020) - Wu, Chunxiao; Selberg, John; Nguyen, Brian; Pansodtee, Pattawong; Jia, Manping; Dechiraju, Harika; Teodorescu, Mircea; Rolandi, Marco
Abstract: A balanced concentration of ions is essential for biological processes to occur. For example, [H + ] gradients power adenosine triphosphate synthesis, dynamic changes in [K + ] and [Na + ] create action potentials in neuronal communication, and [Cl − ] contributes to maintaining appropriate cell membrane voltage. Sensing ionic concentration is thus important for monitoring and regulating many biological processes. This work demonstrates an ion‐selective microelectrode array that simultaneously and independently senses [K + ], [Na + ], and [Cl − ] in electrolyte solutions. To obtain ion specificity, the required ion‐selective membranes are patterned using microfluidics. As a proof of concept, the change in ionic concentration is monitored during cell proliferation in a cell culture medium. This microelectrode array can easily be integrated in lab‐on‐a‐chip approaches to physiology and biological research and applications. Abstract : This work demonstrates an ion‐selective microelectrode array platform for cell culture environment monitoring. The fabrication of the device involves a sequence of steps, including photolithography for patterning traces, electrodeposition for surface modification, and a unique microfluidic strategy for membrane patterning. The system enables simultaneous recording of the ion concentrations of Na +, K +, and Cl − with high sensitivity and selectivity.